Analisis Evaporasi Awan Cumulonimbus di Lapisan Troposfer serta Potensi Terjadinya Curah Hujan Tinggi di Kabupaten Serang - Inayah, Lailatul; Ruhiat, Yayat; M., Yus Rama Denny (Universitas Sultan Ageng Tirtayasa, 2025)
Rain occurs after passing through several stages of the process, which becomes a repetitive cycle; the stages passed are evaporation (evaporation), condensation, and precipitation. Clouds are an element that becomes a factor that affects weather changes, and their shape can change depending on the type. The type of cloud that can cause bad weather is the Cumulonimbus cloud. This research aims to review the volume of rainfall in the Serang Regency area, which can be used as material to predict the steps that must be taken to prevent an event. This research uses data from the Geospatial Information Agency and CHIRPS, which is then processed in ArcGIS 10.8 software. And also based on previous research literature. The data obtained is then analyzed in the ArcGIS application by overlaying one data with other data to find the areas that experience high rainfall. It was found that the average high rain occurred in the western region of Serang Regency.